The phreatic aquifer In the coastal dunes of southwestern Buenos Aires province, Argentina: factors conditioning groundwater quality - Ruffo, Andrés Gabriel (2021)
In the southwest of the province of Buenos Aires, a chain of coastal dunes contains a phreatic aquifer, which is the only sourceof drinking water in most of the seaside cities. The objective of this study is to analyze the geological, hydrogeological andanthropic activities that affect the quality of groundwater for human consumption, between the cities of Monte Hermoso andPunta Alta. Methodologically, the research is developed based on the study of antecedent information, field recognition, wellcensus, cutting analysis, interpretation of electrical tomography and hydrochemical data. The results relate the quality ofthe groundwater with the lithological and stratigraphic characteristics of the area, recognizing the natural presence of traceelements such as F, As, Fe and Mn as well as undesirable organoleptic characteristics (smell, color and taste). In addition, theoccupation of the land with potentially contaminating anthropic actions (cesspool or absorbent wells, farmyards, open-airdumps, etc.) is observed. This research aims to contribute to hydrogeological knowledge, providing the conceptual basis forthe exploitation and management of the aquifer, in an area where water supply is entirely based on the groundwater resource.